2017
DOI: 10.1175/bams-d-15-00255.1
|View full text |Cite
|
Sign up to set email alerts
|

A Containerized Mesoscale Model and Analysis Toolkit to Accelerate Classroom Learning, Collaborative Research, and Uncertainty Quantification

Abstract: Numerical weather prediction (NWP) experiments can be complex and time consuming; results depend on computational environments and numerous input parameters. Delays in learning and obtaining research results are inevitable. Students face disproportionate effort in the classroom or beginning graduate-level NWP research. Published NWP research is generally not reproducible, introducing uncertainty and slowing efforts that build on past results. This work exploits the rapid emergence of software container technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Peng et al, 2014;Arora, 2014, 2016;Melton et al, 2015). The fire subroutine has been extensively eval-uated as part of the Fire Model Intercomparison Project (FireMIP; Hantson et al, 2016;Forkel et al, 2019) in addition to being used to estimate carbon cycle implications of the reduction in global wildfire since the 1930s . The parameterization for competition between PFTs has been evaluated at the site level (Shrestha et al, 2016) as well as at the global scale (Melton and Arora, 2016).…”
Section: Model Biogeochemistry: Ctemmentioning
confidence: 99%
“…Peng et al, 2014;Arora, 2014, 2016;Melton et al, 2015). The fire subroutine has been extensively eval-uated as part of the Fire Model Intercomparison Project (FireMIP; Hantson et al, 2016;Forkel et al, 2019) in addition to being used to estimate carbon cycle implications of the reduction in global wildfire since the 1930s . The parameterization for competition between PFTs has been evaluated at the site level (Shrestha et al, 2016) as well as at the global scale (Melton and Arora, 2016).…”
Section: Model Biogeochemistry: Ctemmentioning
confidence: 99%
“…Particularly for highly non-linear case studies, the goal is not exact reproducibility, but rather enough output to understand the environmental state that forced, and the impacts of, the features being investigated. There may be unique projects in which bitwise reproducibility is deemed necessary; in those cases, containerization can be useful (Hacker et al, 2016). However, to build upon prior research, most knowledge production research does not require bitwise reproducibility.…”
Section: Determining What To Preserve and Sharementioning
confidence: 99%
“…Advantages of the containerization of geoscience models are discussed in many papers (e.g., Hacker et al, 2017 andMelton et al, 2020) and will be shown throughout this paper, including easy installation, high portability, and perfect reproducibility. We want to add one additional advantage that motivates innovation and spurs model development.…”
Section: Containerizationmentioning
confidence: 99%
“…Assuring easy access to the infrastructure will help achieve cooperation. In an educational setting, Hacker et al (2017) has shown that better access to a mesoscale model benefits classroom learning. Better access to unified modeling systems can greatly improve learning experience.…”
mentioning
confidence: 99%